ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP AUDITOR SWITCHING - Ratih Permatasari; Hotman Tohir Pohan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
Auditor switching could happen mandatorily (because of the rules which persistent it and also voluntarily. Many question rise when a company voluntarily switches its auditor because happen outside rules which has been specified. This research aims to analyze the effect of audit firm size, financial distress, public ownership, management turnover, changes in audit committee, audit opinion, audit fee on auditor switching in Indonesia. Data collecting method which used in this research is method purposive sampling, that based on the objectives of research. ,Based on method purposive sampling, research sample total is 180 manufacturing companies which is listed in "Bursa Efek Indonesia" (BEI) in 2009-2014 period. Hypothesis in this research are tested by logistics regression analytical method. Result of this research shows that variables having which significantly effect the auditor switching are audit firm size and management turnover. On the other hand, other variables in this research like audit firm size, client size, client growth rate, financial distress, board of commissioners, and audit opinion do not have significant effect on company decision to do auditor switching.